Genomic analysis of non-carbapenem drug-resistant Gram-negative bacteria from advanced chronic liver disease (ACLD) patients suggests no evidence for in-house transmissions - Best, Christopher D.; Nemati, Zahra; Schultze, Tilman; Hogardt, Michael; Cadoli, Camilla; Mücke, Marcus M.; Wiedemann, Toska; Erasmus, Hans-Peter; Welsch, Christoph; Kempf, Volkhard A. J. (Frontiers in Microbiology, 2026)
BackgroundIn advanced chronic liver disease (ACLD) patients, bacterial infections with multidrug-resistant Gram-negative bacteria (MDRGN) can progress to acute-on-chronic liver failure (ACLF) with high mortality rates. Particularly carbapenem-resistant Gram-negative bacteria (CR-GN) pose a significant threat due to limited antibiotic treatment options. However, non-carbapenem drug-resistant Gram-negative bacteria (NCR-DRGN) are clinically highly relevant, as they occur more frequently and may serve as precursors to CR-GN. This study aims to assess the prevalence, resistance mechanisms, and transmission dynamics of NCR-DRGN in ACLD patients including those with ACLF.Materials and methodsA prospective, single-center study was conducted at University Hospital Frankfurt. Over 32 months, ACLD patients were screened for NCR-DRGN by routine microbiology techniques. Whole-genome sequencing (WGS) of isolated bacteria was performed to analyze genetic diversity, resistance, and transmission patterns. Epidemiological links were explored through patient chart reviews.ResultsNCR-DRGN were found in 12.1% (n = 22/182) of ACLD patients, comprising of 44 isolates, predominantly Escherichia coli (n = 40/44; 90.9%). All isolates were phenotypically classified as NCR-DRGN; however, one isolate was found to harbor a blaOXA–244 gene potentially affecting carbapenem treatment efficacy. Genomic analysis revealed significant diversity, with no evidence of clonal outbreaks, although one potential transmission event was identified.ConclusionNCR-DRGN are prevalent in ACLD patients, with E. coli as the dominant pathogen. Standard hygiene measures appear effective in preventing transmission, emphasizing the importance of routine screening and infection control in this high-risk population.